Critical Thinking Skills (CTS) through Augmented Reality Worksheets using The Inquiry-Scaffolding Models - Ardhi Saputri, Affa; Ellany Mohtar, Lilia; Arsini, Arsini; Said Prastyo, Irman; Surya Fitra, Ilham (Faculty of Science and Education, UIN Walisongo Semarang, 2024)
Critical thinking skills (CTS) are important for training in physics. This research aims to train students' CTS through augmented reality worksheets with the inquiry-scaffolding model. The research participants comprised 36 third-semester physics education students at UIN Walisongo Semarang. This research utilized a pre-experimental method employing a one-group pre-test post-test design. The enhanced CTS was assessed using the N-gain test. The analysis of students' CTS yielded four categories: very less critical, less critical, critical, and very critical. Implementing learning through augmented reality worksheets employing an inquiry-scaffolding model enhanced students' CTS by 0.30 with moderate criteria. The breakdown of students' CTS following the augmented reality worksheets with inquiry-scaffolding models showed a distribution of 19.44% less critical, 69.44% critical, and 11.11% very critical. From the research findings, it can be concluded that augmented reality worksheets using the inquiry-scaffolding model effectively train students' CTS in learning physics. Through learning with augmented reality worksheets, students are trained to analyze arguments, consider the validity of various sources, make inferences and general conclusions, and make decisions. Scaffolding procedure: explaining, modeling, and questioning can provide an overview of cause and effect, and abstraction of a concept as a provision to strengthen CTS.